Analysis of Hematological Profile of Catfish (Clarias sp.) as a Health Indicator Use of Hemolyzer for Aquatic Animals - Maria Agustina Pardede; Muhammad Abdul Aziz; Dian Putri Apriliani; Dwi Retna Kumalaningrum; Dewi Ambarwati; Farida Maulidia; Alin Asyabil; Muhammad Hilmy Maulana (Juvenil, 2025)
ABSTRACTThe hematological profile of catfish (Clarias sp.) is a critical indicator of health and well-being in aquaculture practices. This study aimed to analyze the hematological parameters of catfish under aquaculture conditions using two different hematology analyzers: Hemolyzer 3 Pro and Veterinary Hematology Analyzer Mindray Series BC2800Vet. Blood samples were collected from the caudal vein, anticoagulated with EDTA, and analyzed for red blood cell count (RBC), white blood cell count (WBC), hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), and platelet count (PLT). Results indicated significant variations between the analyzers. The Hemolyzer 3 Pro indicated elevated levels, with Hb ranging from 15.7 to 16.7 g/dl, RBC from 2.66 to 2.79 × 10^6/mm³, and WBC from 92,200 to 98,040 × 10^6/mm³, suggesting possible polycythemia and an active immune response. In contrast, the Mindray Analyzer reported values within the normal range, with Hb at 7.2 g/dl, RBC at 1.43 × 10^6/mm³, and WBC at 46,100 × 10^6/mm³, implying stable health conditions. The study also observed monocytosis, indicative of potential chronic inflammation or infection. These discrepancies highlight the importance of standardized methodologies in hematological assessments. Regular monitoring of hematological parameters is essential for early disease detection and effective management in aquaculture. Further research is recommended to explore the underlying causes of these variations and to optimize health management strategies for catfish in aquaculture systems.Keywords: Aquaculture, Catfish, Haemolyzer, Hematology